As Marchas da Família com Deus pela Liberdade e o golpe de 1964 - Presot, Aline Alves (2004)
The main purpose of this research is investigate one of the most important manifestations of the Brazilian political history. As a social phenomenon, the “Marchas” can be understood as part of the opposition to the João Goulart’s nationalist government. To the organizers of the “Marchas”, the Brazilian president João Goulart had comunist inclinations and was trying to destroy the religious, patriotic and moral values of the Brazilian society. The “Marchas” were a kind of act of asking for intervention to the Armed Forces to save the Brazilian institutions. After March the 31, 1964, the “Marchas” were re-defined and became part of the justifications of the coup d’état.